Pengaruh Return On Asset (Roa), Leverage, Intensitas Modal, Dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Retno Anggraeny Agustin; Hedi Pandowo; Dian Kusumaningrum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Tax aggressiveness is a company's effort to reduce the tax burden. The reduction in taxes was due to differences in interests between companies and the government. This study aims to determine the effect of return on asset, leverage, capital intensity, and company size on tax aggressiveness. This study uses agency theory. This theory relates to the relationship between principal and agent. This type of research is quantitative using secondary data sources in the form of annual financial reports through the Indonesia Stock Exchange (IDX). The population used in this study were property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2018-2022 as many as 53 companies. The sampling technique in this study used purposive sampling with 3 specified research criteria so that a sample size of 12 companies was obtained with 60 data obtained. The data analysis technique used was multiple linear regression analysis using the SPSS version 24 application program. The results of the study showed that partially leverage, capital intensity and company size had a significant effect on tax aggressiveness, while return on assets did not have a significant effect on tax aggressiveness. To get better results in subsequent research, the population can be expanded to include more samples and other variables such as liquidity and corporate social responsibility can be used